ISCHEMIC STROKE SYMPTOMS AND TREATMENT - Begbutayeva Sokhila Bakhtiyor kizi; Eshpulatov Sherbek Sunnatullo ugli; Musurmonova Guzaloy Olmosovna; Eshankulova Zebiniso Zokirjon kizi; Kasimov Arslanbek Atabayevich; Mamurova Mavludakhon Mirkhamzayevna (Western European Studies, 2024)
Stroke is a collective term referring to several types of cerebral circulatory disorders: ischemic stroke (aka brain infarction), hemorrhagic stroke (cerebral hemorrhage), venous infarction, and subarachnoid hemorrhage (bleeding into the space between the inner and middle layer of tissue covering the brain).
Keywords: Physical rehabilitation; upper limb function; inner